Extended range of the Lockheed Martin Mini cryocooler. (December 2017) - Frank, D.; Sanders, L.; Nason, I.; Mistry, V.; Guzinski, M.; Roth, E.; Olson, J.R.
Highlights: Design based on unit originally developed for NASA and higher capacity unit for ESA. The unit is in a split configuration with the cold head separated from the compressor. Cold head arranged in U shape with inertance coil in plenum on warm flange. This unit provides a compact system for many actively cooled instruments. Abstract: This paper describes the expanded performance range of the Lockheed Martin Mini cryocooler thermal mechanical unit (TMU). The design is based on the standard unit originally developed for NASA and a higher capacity developed for ESA. These higher capacity Mini units are in a split configuration with the cold head separated from the compressor. The TMU provides cooling over a wide range of temperatures with a weight of 1.9 kg including the 1.4 kg compressor and the 0.45 kg cold head. The unit provides for 3.5 W cooling at 105 K and approximately 7 W cooling at 150 K for 293 K reject temperature with 60 W of input power.